Inventory COntrol Optimization of Datang Jual Beli (DJB) Shop as A Startup Company - Anggrianto, Jeffy Eugene; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2013)
Internet as one of business means for making money is very popular especially among youngster. Many young people see this opportunity and use it. Although this business need more knowledge about the internet and its relation, but it still attractive. Many executive see â€œtime is moneyâ€ as their motto which also making internet more attractive since everyone, even busy people can chat, shop, or even just browsing from their seat at home or office. Recently internet business is growing a lot more in Asia including Indonesia where the growth of new online business such as online shopping were very fast expanding. This also become one reason for Datang Jual Beli (DJB) Shop to open an online shop which sell gadget and accessories with brand name Dicapac from Korean Supplier. Currently DJB Shop face some problem related with operational matter namely exceed inventory stock problem and delivery product problem. Since delivery product issue already mitigated, then the focus change to the exceed inventory stock issue. Through this research, it is determined that through Fixed order quantity model with safety stock and optimal order quantity can resulted a lower annual cost. This solution is expected to solve the inventory problem as prioritized one and provide some recommendation to be implemented for better operational improvementÂ Keywords : inventory control method, operational, online shop, delivery serviceÂ Â Â